PERANCANGAN APLIKASI MOBILE SISTEM INFORMASI “KIFORM” BERBASIS ANDROID UNTUK MENINGKATKAN EFEKTIFITAS PELAYANAN PUBLIK TERHADAP MASYARAKAT PADA KELURAHAN SUKASARI - Endang Suryana; M. Devi Adiansyah; Imami Fatimatun (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2016)
Sukasari Urban Village is one of the villages located in the district Rajeg Tangerang District, Banten. Currently, the development of information technology very rapidly to take advantage of the android application system as enhancing the effectiveness and flexibility of activities to get the information, in this case related to the public service. It is important to get public information faster in the village Sukasari. Observations on public service activities in the Village Sukasari are less effective if it is not included with public service information applications based on Android. With information still use the public services at the village office mading so is difficult to get information society wards. Also the location of the residence community and urban village office to be the cause. By design kiForm app (android app) as a form of use of information technology will facilitate the public to get information public services wherever they are.